2008
DOI: 10.1038/sj.bjc.6604521
|View full text |Cite
|
Sign up to set email alerts
|

Effects of green tea polyphenol on methylation status of RECK gene and cancer cell invasion in oral squamous cell carcinoma cells

Abstract: RECK is a novel tumour suppressor gene that negatively regulates matrix metalloproteinases (MMPs) and inhibits tumour invasion, angiogenesis and metastasis. In the present study, we investigated the effects of epigallocatechin-3-gallate (EGCG), a major polyphenol in green tea, on the methylation status of the RECK gene and cancer invasion in oral squamous cell carcinoma cell lines. Our results showed that treatment of oral cancer cells with EGCG partially reversed the hypermethylation status of the RECK gene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(116 citation statements)
references
References 34 publications
2
110
0
4
Order By: Relevance
“…Gene promoter hypermethyla tion has been associated with the silencing of tumor-related genes, which is considered the most important epigenetic dis ruption in numerous tumors (18,19). In a previous study, hypermethylation of the RECK gene was partially reversed by epigallocatechin gallate treatment, and the mRNA expression level of RECK was significantly enhanced in oral squamous cell carcinoma cell lines (20). RAS was able to increase the binding of DNA methyltransferase (DNMT) 3B to the RECK promoter and induce promoter methylation, while treatment with 5'-azacytidine and DNMT3B-targeting siRNA restored RECK expression and potently suppressed cell invasion (21).…”
Section: Introductionmentioning
confidence: 98%
“…Gene promoter hypermethyla tion has been associated with the silencing of tumor-related genes, which is considered the most important epigenetic dis ruption in numerous tumors (18,19). In a previous study, hypermethylation of the RECK gene was partially reversed by epigallocatechin gallate treatment, and the mRNA expression level of RECK was significantly enhanced in oral squamous cell carcinoma cell lines (20). RAS was able to increase the binding of DNA methyltransferase (DNMT) 3B to the RECK promoter and induce promoter methylation, while treatment with 5'-azacytidine and DNMT3B-targeting siRNA restored RECK expression and potently suppressed cell invasion (21).…”
Section: Introductionmentioning
confidence: 98%
“…EGCG is a major polyphenol in green tea, and a key active ingredient (19). Previous studies (24,25) have demonstrated that EGCG inhibits DNMT and inhibits the hypermethylation of newly synthesised DNA, resulting in the reversal of hypermethylation and the re-expression of silenced genes, with fewer side effects and toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the dose-and time-dependent changes associated with EGCG treatment, the SACC83 cells were treated in triplicate with EGCG (Wako Pure Chemical Industries, Ltd., Osaka, Japan), as described previously (19). Briefly, the cells were seeded at low density (5x10 5 /100 mm dish) 24 h prior to treatment with EGCG.…”
Section: Introductionmentioning
confidence: 99%
“…RECK activity is down-regulated in several human cancers and is associated with promoter hypermethylation in the gene. In an elegant study, Kato et al (23) investigated how EGCG altered RECK DNA methylation and expression in four human oral squamous cell carcinoma cell lines. Critically, they investigated whether reversing hypermethylation and increasing RECK gene expression could inhibit oral squamous cell carcinoma migration and invasiveness.…”
Section: Epigenetics Diet and Diseasementioning
confidence: 99%